Sailor Character Traits, Personality, and School Management Perceptions: Mental Readiness of Vocational Maritime Students - Rini Nurahaju; Dessy Nur Utami (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Vocational maritime education plays a critical role in preparing students for the psychological and professional demands of seafaring by fostering essential character traits, personality profiles, and perceptions of school management. This study aimed to examine sailor character traits, Big Five personality profiles, and school management perceptions among vocational maritime students in Surabaya, Indonesia, to understand their readiness for maritime careers. A descriptive quantitative approach was employed, involving 96 students who completed questionnaires on character traits, personality, and school management perceptions, with data analyzed using the Statistical Package for the Social Sciences. The findings revealed that discipline was the most prioritized trait at 66%, followed by vigilance at 42%, while 53.1% of students exhibited moderate conscientiousness in their personality profiles. School management was perceived as moderately effective by 49% of students, with teaching innovation rated highest. These results indicate that vocational maritime education effectively cultivates traits and psychological readiness for seafaring, though improvements in school management are needed. The study highlights the importance of strengthening character-building and personality development programs to enhance students’ mental preparedness for maritime professions.